Pemanfaatan Media Sosial - budi budi budi; Ernita Arif; Elva Ronaning Roem (Jurnal Ranah Komunikasi, 2019)
The rapid advancement of technology and information has become a challenge for the development of libraries today. In its research UNESCO stated that the index of reading interest in Indonesian people was concern only 0,001%, meaning that there were only one person from a thousand Indonesian people (Liputan6.com, 2017). In order for libraries to be of interest to people in the current technological era, one needs to do various innovations, one of which is in promotional activities so that the public knows and knows the services that are in the library and ultimately uses them. The use of social media as a means of promotion of the East Belitung Regency library is very important, because today’s society is not separated from the use of social media as a means of information and communication. This study aims to determine the use of social media as a means of promoting the library in the Regional Public Library of East Belitung Regency. The research method used in qualitative with a descriptive approach, by describing the object of research based on facts in the field and using informant as a source of data by conducting interviews, observation and documentation. Based on the research conducted, it shows that the use of social media as a means of promoting the East Belitung Regency library results includes four things, namely: website, social networking (Facebook and Instagram) and YouTube.